Development of web application package to design AC substation grounding system based on IEE STD. 80-2000 for continuous education and professional training - Mohammed Aldebry, Mohammed Alsanosi (2016)
Substation grounding is a very important aspect in a substation design which forms a safe grounding grid system besides functioning as a means of dissipating currents to the surrounding ground during normal and fault conditions, also prevents the ground potential rise during a fault from creating dangerous potential gradients on the substation ground surface that can endanger a life of a person in the vicinity of the grounded facility. This grounding study is based on IEEE Standard 80-2000 (Revision of IEEE Std. 80-1986) which serves as a guide to the safety in ac substation grounding. With the fast growing of the use on the Internet technology and the daily use of it in all life routines including education, it will be necessary and interesting to provide a learning and educational web application for the Internet users especially the engineers of them.